Composite junction layer, multi-junction tandem solar cell and method of making the same

CN122719280APending Publication Date: 2026-09-08ZHONGSHAN DEHUA CHIP TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610842133.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-11
Publication Date
2026-09-08

AI Technical Summary

Technical Problem

[0004]1、ITO在近红外波段(GaInAs的主要吸光区)的寄生吸收会显著降低光电流;同时,ITO与上下层材料的能级匹配不理想,会导致开路电压与填充因子损失;

Benefits of technology

[0038] 1. This invention utilizes Au metal nanoparticles/PEDOT:PSS/high work function oxide (MoO) X The three-layer stacked structure of the material forms a division of labor of "conduction-transportation-selection". The Au nanoparticle conductive layer improves conductivity, the PEDOT:PSS interface buffer layer achieves interface smoothing and buffering, and the MoO layer... X The energy level matching layer is responsible for achieving ideal energy level matching with the perovskite valence band, maximizing hole extraction efficiency. The synergistic function of the three materials in conductivity, interface buffering and energy level matching achieves comprehensive performance that cannot be achieved by a single or double-layer structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122719280A_ABST
    Figure CN122719280A_ABST
Patent Text Reader

Abstract

The application discloses a composite connecting layer, a multi-junction laminated solar cell and a preparation method thereof. X The Au nano-particle conductive layer has a light transmittance of more than 90% and a thickness of 5-20 nm; the PEDOT:PSS interface buffer layer has a thickness of 20-60 nm; and the MoO X The energy level matching layer has a thickness of 5-15 nm. X The three-layer stacking design of the Au metal nano-particle / PEDOT:PSS / MoO The complementary functions and synergistic effect of the three materials effectively solve the problems of the traditional connecting layer in conductivity, interface morphology and energy level matching.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of optoelectronic devices, and in particular to a composite interconnect layer, a multi-junction tandem solar cell, and its fabrication method. Background Technology

[0002] Tandem solar cells constructed from III-V group / perovskite materials achieve highly efficient utilization of the solar spectrum through optimized bandgap engineering design. The synergistic operation of the wide-bandgap perovskite top cell (1.78–1.9 eV), the narrow-bandgap GaInAs middle cell (1.12–1.42 eV), and the Ge bottom cell enables the device to effectively capture the solar spectrum in the range of 300–1700 nm, significantly enhancing its photoelectric conversion potential.

[0003] One of the keys to achieving high-efficiency stacked devices lies in high-performance intermediate interconnect layers. Currently, common solutions are mostly based on single or double-layer materials, such as transparent conductive oxide (ITO), ultrathin metal films, or conductive polymers like PEDOT:PSS. However, these materials all have the following significant limitations in the perovskite / GaInAs system:

[0004] 1. Parasitic absorption of ITO in the near-infrared band (the main light absorption region of GaInAs) will significantly reduce photocurrent; at the same time, the energy level matching between ITO and the upper and lower layer materials is not ideal, which will lead to loss of open circuit voltage and fill factor.

[0005] 2. Ultrathin metal films have pinholes and high optical loss;

[0006] 3. Single PEDOT:PSS faces problems such as insufficient conductivity, poor matching with perovskite energy levels (leading to open-circuit voltage loss), and its acidity may corrode sensitive interfaces.

[0007] 4. PEDOT: The lateral conductivity of the PSS+oxide bilayer is severely insufficient, the interface morphology of the metal mesh+oxide bilayer is poor, and the quality of the perovskite film is difficult to guarantee. Summary of the Invention

[0008] The primary objective of this invention is to overcome the shortcomings of existing technologies and provide a composite bonding layer employing "Au metal nanoparticles / PEDOT:PSS / MoO". X "The three-layer stacked design effectively solves the problems of traditional connecting layers in terms of conductivity, interface morphology and energy level matching through the complementary and synergistic effects of the three materials."

[0009] The second objective of this invention is to provide a III-V compound / perovskite multi-junction tandem solar cell and its preparation method.

[0010] The first objective of this invention is achieved through the following technical solution:

[0011] A composite bonding layer for III-V compound / perovskite multi-junction tandem solar cells comprises, from bottom to top, an Au nanoparticle conductive layer, a PEDOT:PSS interface buffer layer, and a MoO layer stacked sequentially. X Energy level matching layer; the Au nanoparticle conductive layer has a transmittance >90% and a thickness of 5~20nm; the PEDOT:PSS interface buffer layer has a thickness of 20~60nm; the MoO X The thickness of the energy level matching layer is 5~15nm.

[0012] The second objective of this invention is achieved through the following technical solution:

[0013] A III-V compound / perovskite multi-junction tandem solar cell includes a Ge substrate, a GaInP nucleation layer, a GaInAs buffer layer, a GaAs / AlGaAs tunnel junction, a GB strain relief layer, and an Al... 0.25 Ga (1-Xn) In Xn As BSF layer, p-type Ga (1-Xn) In Xn As base region, n-type Ga (1-Xn) In Xn As emitter region, AlInP window layer, n-type Ga (1-Xn) In Xn The structure comprises an As cap layer, a hole transport layer, a perovskite active layer, an electron transport layer, and a top electrode, as well as the aforementioned composite interconnect layer; the Ge substrate, GaInP nucleation layer, GaInAs buffer layer, GaAs / AlGaAs tunnel junction, GB strain relief layer, and Al... 0.25 Ga (1-Xn) In Xn As BSF layer, p-type Ga (1-Xn) In Xn As base region, n-type Ga (1-Xn) In Xn As emitter region, AlInP window layer, n-type Ga (1-Xn) In Xn The As cap layer, composite bonding layer, hole transport layer, perovskite active layer, electron transport layer and top electrode are stacked sequentially from bottom to top.

[0014] Furthermore, the GaInP nucleation layer is grown at a temperature of 600~650℃, has a thickness of 5~20nm, and a Si doping concentration of 2E18~5E18cm⁻¹. -3 The GaInAs buffer layer is grown at a temperature of 600~650℃, has a thickness of 5~20nm, and a Si doping concentration of 1E18~3E18cm⁻¹. -3 .

[0015] Furthermore, the growth temperature of the GaAs / AlGaAs tunnel junction is 600~650℃, and it comprises GaAs layers and AlGaAs layers stacked sequentially; wherein the thickness of the GaAs layer is 10~20nm, and the Si doping concentration is 1E19~3E19cm. -3 The AlGaAs layer has a thickness of 5-15 nm and a C doping concentration of 3E19-9E19 cm⁻¹. -3 .

[0016] Furthermore, the GB strain relief layer comprises N sequentially stacked Al layers. 0.25 Ga (1-Xi) In Xi As layers and their stacking configurations are located on N Al layers. 0.25 Ga (1-Xi) In Xi Al at the top of As layer 0.25 Ga (0.96-Xn) In (Xn+0.04) As layer; where i = 1, 2, 3, ..., N, N Al 0.25 Ga (1-Xi) In Xi In the As layer, the In composition Xi ranges from 0.01 to 0.21, gradually changing along the stacking direction, and each Al layer... 0.25 Ga (1-Xi) In Xi The thickness of the As layers is consistent, or the thickness of each layer increases with the increase of the In content; Al 0.25 Ga (1-Xi) In Xi The growth temperature of the As layer is 600~650℃, and all Al 0.25 Ga (1-Xi) In Xi The total thickness of the As layer is 1000~2000 nm, and the Zn doping concentration is 5E17~1E18 cm⁻¹. -3 The Al 0.25 Ga (0.96-Xn) In (Xn+0.04) The As layer is grown at a temperature of 600~650℃, with a thickness of 500~1500nm, and the Zn doping concentration is 5E17~1E18cm. -3 .

[0017] Furthermore, the Al 0.25 Ga (1-Xn) In Xn The As-BSF layer is grown at a temperature of 600~650℃, with a thickness of 100~300nm, and a Zn doping concentration of 1E18~3E18cm⁻¹. -3 The p-type Ga (1-Xn) In XnThe As-based region is grown at a temperature of 600–650 °C, with a thickness of 500–2000 nm, and a Zn doping concentration of 1E¹⁷–1E¹⁸ cm⁻¹. -3 The n-type Ga (1-Xn) In Xn The As emitter region is grown at a temperature of 600~650℃, with a thickness of 100~300nm, and the Si doping concentration is 1E18~5E18cm⁻¹. -3 The AlInP window layer is grown at a temperature of 600~650℃, has a thickness of 30~100nm, and a Si doping concentration of 1E18~8E18cm⁻¹. -3 The n-type Ga (1-Xn) In Xn The As cap layer is grown at a temperature of 600~650℃ with a thickness of 50~100nm, and the Si doping concentration is 1E18~5E18cm⁻¹. -3 .

[0018] Furthermore, the material of the hole transport layer is selected from NiO. x doped NiO x The thickness is 10~30nm and is composed of one or any combination of two of the following: CuSCN and 4PACz-based monomolecular self-assembled layers.

[0019] Furthermore, the perovskite active layer is a wide-bandgap perovskite material FA with a voltage of 1.78~1.9 eV. t MA y Cs z Pb 2-t-y- z I w Br 1-w The thickness is 500~1500nm, wherein the FA content (t) is 0.45~0.9, the MA content (y) is 0~0.2, the Cs content (z) is 0.05~0.4, and t + y + z = 1, and the I content (w) is 0.6~0.85; the material of the electron transport layer is selected from SnO2, 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline, C 60 The material of the top electrode is selected from one or any combination of two of the following: silver prepared by electron beam evaporation and TCO material prepared by magnetron sputtering, with a thickness of 10-30 nm.

[0020] A method for fabricating a III-V compound / perovskite multi-junction tandem solar cell includes the following steps:

[0021] S1. Transfer the Ge substrate into the MOCVD process; wherein the Ge substrate is a P-type Ge substrate or an N-type Ge substrate;

[0022] S2. Using a growth temperature of 600~650℃, an epitaxial GaInP nucleation layer with a thickness of 5~20nm is grown on the upper surface of a Ge substrate, and the Si doping concentration is 2E18~5E18cm⁻¹. -3 ;

[0023] S3. Using a growth temperature of 600~650℃, an epitaxial GaInAs buffer layer with a thickness of 5~20nm is grown on the upper surface of the GaInP nucleation layer, and the Si doping concentration is 1E18~3E18cm. -3 ;

[0024] S4. Using a growth temperature of 600~650℃, a GaAs / AlGaAs tunnel junction is epitaxially grown on the upper surface of the GaInAs buffer layer; the GaAs / AlGaAs tunnel junction comprises GaAs layers and AlGaAs layers stacked sequentially; wherein the thickness of the GaAs layer is 10~20nm, and the Si doping concentration is 1E19~3E19cm. -3 The AlGaAs layer has a thickness of 5-15 nm and a C doping concentration of 3E19-9E19 cm⁻¹. -3 ;

[0025] S5. Using a growth temperature of 600~650℃, an epitaxial GB strain-relieving layer is grown on the upper surface of the GaAs / AlGaAs tunnel junction; the GB strain-relieving layer comprises N sequentially stacked Al... 0.25 Ga (1-Xi) In Xi As layers and their stacking configurations are located on N Al layers. 0.25 Ga (1-Xi) In Xi Al at the top of As layer 0.25 Ga (0.96-Xn) In (Xn+0.04) As layer; where i = 1, 2, 3, ..., N, N Al 0.25 Ga (1-Xi) In Xi In the As layer, the In composition Xi ranges from 0.01 to 0.21, gradually changing along the stacking direction, and each Al layer... 0.25 Ga (1-Xi) In Xi The thickness of the As layers is consistent, or the thickness of each layer increases with the increase of the In content; all Al 0.25 Ga (1-Xi) In Xi The total thickness of the As layer is 1000~2000 nm, and the Zn doping concentration is 5E17~1E18 cm⁻¹. -3 The Al 0.25 Ga (0.96-Xn) In (Xn+0.04)The As layer is grown at a temperature of 600~650℃, with a thickness of 500~1500nm, and the Zn doping concentration is 5E17~1E18cm. -3 ;

[0026] S6. Al was epitaxially grown on the upper surface of the GB strain-relief layer at a growth temperature of 600~650℃. 0.25 Ga (1-Xn) In Xn The As BSF layer has a thickness of 100~300nm and a Zn doping concentration of 1E18~3E18cm. -3 ;

[0027] S7, using a growth temperature of 600~650℃, in Al 0.25 Ga (1-Xn) In Xn p-type Ga is epitaxially grown on the upper surface of the BSF layer. (1-Xn) In Xn The As base region has a thickness of 500~2000 nm and a Zn doping concentration of 1E17~1E18 cm⁻¹. -3 ;

[0028] S8. A growth temperature of 600~650℃ is used in p-type Ga... (1-Xn) In Xn n-type Ga epitaxial growth on the upper surface of the As-based region (1-Xn) In Xn The As emitter region has a thickness of 100~300 nm, and the Si doping concentration is 1E18~5E18 cm⁻¹. -3 ;

[0029] S9. A growth temperature of 600~650℃ is used in n-type Ga... (1-Xn) In Xn An AlInP window layer with a thickness of 30–100 nm is epitaxially grown on the upper surface of the As emitter region, and the Si doping concentration is 1E¹⁸–8E¹⁸ cm⁻¹. -3 ;

[0030] S10. Using a growth temperature of 600~650℃, n-type Ga is epitaxially grown on the upper surface of the AlInP window layer. (1-Xn) In Xn The As cap layer has a thickness of 50~100nm, and the Si doping concentration is 1E18~5E18cm. -3 An epitaxial wafer is thus prepared, and then the epitaxial wafer is taken out from MOCVD, and a metal electrode is prepared on its lower surface to form an ohmic contact.

[0031] S11, in n-type Ga (1-Xn) In Xn A composite bonding layer is deposited on the upper surface of the As cap layer;

[0032] S12. A hole transport layer is prepared on the upper surface of the composite bonding layer using a spin-coating process. The material of the hole transport layer is selected from NiO. x doped NiO x One or any combination of two of the following: CuSCN and 4PACz-based monomolecular self-assembled layers, with a thickness of 10~30 nm;

[0033] S13. A perovskite active layer is prepared on the upper surface of the hole transport layer using a spin-coating process. The perovskite active layer is a wide-bandgap perovskite material FA with a voltage of 1.78~1.9 eV. t MA y Cs z Pb 2-t-y-z I w Br 1-w Its thickness is 500~1500nm;

[0034] S14. An electron transport layer is prepared on the upper surface of the perovskite active layer using a spin-coating process. The material of the electron transport layer is selected from SnO2, 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline, and C. 60 One or any combination of two of them, with a thickness of 10~30nm;

[0035] S15. A top electrode is fabricated on the electron transport layer. The material of the top electrode is selected from one or a combination of two of the following: silver prepared by electron beam evaporation and TCO material prepared by magnetron sputtering. The thickness of the top electrode is 100~250nm.

[0036] Furthermore, in step S11, firstly in the n-type Ga (1-Xn) In Xn Au nanoparticle colloidal dispersion is spin-coated onto the upper surface of the As cap layer to form a uniform Au nanoparticle conductive layer with a transmittance >90% and a thickness of 5-20 nm. Next, a PEDOT:PSS solution doped with 5% EG is spin-coated onto the upper surface of the Au nanoparticle conductive layer to completely cover the Au particles, forming a smooth, pinhole-free PEDOT:PSS interface buffer layer with a thickness of 20-60 nm. Finally, a continuous MoO layer is formed on the upper surface of the PEDOT:PSS interface buffer layer using physical vapor deposition or atomic layer deposition. X Energy level matching layer, the MoO X The thickness of the energy level matching layer is 5~15nm.

[0037] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0038] 1. This invention utilizes Au metal nanoparticles / PEDOT:PSS / high work function oxide (MoO) X The three-layer stacked structure of the material forms a division of labor of "conduction-transportation-selection". The Au nanoparticle conductive layer improves conductivity, the PEDOT:PSS interface buffer layer achieves interface smoothing and buffering, and the MoO layer... X The energy level matching layer is responsible for achieving ideal energy level matching with the perovskite valence band, maximizing hole extraction efficiency. The synergistic function of the three materials in conductivity, interface buffering and energy level matching achieves comprehensive performance that cannot be achieved by a single or double-layer structure.

[0039] 2. This invention employs a "point-surface-surface" three-dimensional charge channel design, innovatively constructing Au nanoparticles (point contact collection), PEDOT:PSS (surface transport), and MoO2. X (Surface selection) Three-dimensional charge pathway. While ensuring high light transmittance, it achieves ultra-high lateral conductivity and efficient longitudinal hole extraction, significantly improving the battery's fill factor and short-circuit current.

[0040] 3. The Au nanoparticle conductive layer and PEDOT:PSS interface buffer layer of the present invention can be prepared by a low-temperature solution method (such as spin coating), requiring only the final step of MoO. X Deposition avoids high temperatures or complex photolithography steps, reducing costs and simplifying the process. Attached Figure Description

[0041] Figure 1 This is a schematic diagram of the composite connecting layer of the present invention.

[0042] Figure 2 This is a schematic diagram of the structure of the multi-junction stacked solar cell of the present invention.

[0043] Figure 3 This is a schematic diagram of the GB strain relief layer of the present invention. Detailed Implementation

[0044] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0045] Example 1:

[0046] like Figure 1As shown, this embodiment provides a composite connection layer for III-V compound / perovskite multi-junction tandem solar cells, comprising, from bottom to top, an Au nanoparticle conductive layer 1101, a PEDOT:PSS interface buffer layer 1102, and a MoO2 layer, which are stacked sequentially. X Energy level matching layer 1103; the Au nanoparticle conductive layer 1101 has a transmittance >90% and a thickness of 5~20nm; the PEDOT:PSS interface buffer layer 1102 has a thickness of 20~60nm; the MoO X The thickness of the energy level matching layer 1103 is 5~15nm.

[0047] Example 2:

[0048] This embodiment provides a composite interconnect layer for III-V compound / perovskite multi-junction tandem solar cells. The difference between this embodiment and Embodiment 1 is that the metal nanoparticles in the Au nanoparticle conductive layer are replaced by a metal mesh, and the metal can be Au, Ag, or Cu; MoO X MoOx in the energy level matching layer is replaced with V2O5.

[0049] Example 3:

[0050] like Figure 2 As shown, this embodiment provides a III-V compound / perovskite multi-junction tandem solar cell, including a Ge substrate 1, a GaInP nucleation layer 2, a GaInAs buffer layer 3, a GaAs / AlGaAs tunnel junction 4, a GB strain relief layer 5, and an Al... 0.25 Ga (1-Xn) In Xn As BSF layer 6, p-type Ga (1-Xn) In Xn As base region 7, n-type Ga (1-Xn) In Xn As emitter region 8, AlInP window layer 9, n-type Ga (1-Xn) In Xn The structure comprises an As cap layer 10, a hole transport layer 12, a perovskite active layer 13, an electron transport layer 14, and a top electrode 15, as well as the composite interconnect layer described in Example 1 or 2; the Ge substrate 1, GaInP nucleation layer 2, GaInAs buffer layer 3, GaAs / AlGaAs tunnel junction 4, GB strain relief layer 5, and Al... 0.25 Ga (1-Xn) In Xn As BSF layer 6, p-type Ga (1-Xn) In Xn As base region 7, n-type Ga (1-Xn) In Xn As emitter region 8, AlInP window layer 9, n-type Ga (1-Xn)In Xn The As cap layer 10, composite bonding layer, hole transport layer 12, perovskite active layer 13, electron transport layer 14 and top electrode 15 are stacked sequentially from bottom to top.

[0051] The growth temperature of GaInP nucleation layer 2 is 600~650℃, the thickness is 5~20nm, and the Si doping concentration is 2E18~5E18cm. -3 .

[0052] The GaInAs buffer layer 3 is grown at a temperature of 600~650℃, with a thickness of 5~20nm and a Si doping concentration of 1E18~3E18cm⁻¹. -3 .

[0053] The GaAs / AlGaAs tunnel junction 4 is grown at a temperature of 600~650℃ and consists of GaAs and AlGaAs layers stacked sequentially; wherein the thickness of the GaAs layer is 10~20nm and the Si doping concentration is 1E19~3E19cm. -3 The AlGaAs layer has a thickness of 5-15 nm and a C doping concentration of 3E19-9E19 cm⁻¹. -3 .

[0054] like Figure 3 As shown, the GB strain relief layer 5 comprises N sequentially stacked Al layers. 0.25 Ga (1-Xi) In Xi As layers and their stacking configurations are located on N Al layers. 0.25 Ga (1-Xi) In Xi Al at the top of As layer 0.25 Ga (0.96-Xn) In (Xn+0.04) As layer; where i = 1, 2, 3, ..., N, N Al 0.25 Ga (1-Xi) In Xi In the As layer, the In composition Xi ranges from 0.01 to 0.21, gradually changing along the stacking direction, and each Al layer... 0.25 Ga (1-Xi) In Xi The thickness of the As layers is consistent, or the thickness of each layer increases with the increase of the In content; Al 0.25 Ga (1-Xi) In Xi The growth temperature of the As layer is 600~650℃, and all Al 0.25 Ga (1-Xi) In Xi The total thickness of the As layer is 1000~2000 nm, and the Zn doping concentration is 5E17~1E18 cm⁻¹. -3 The Al 0.25Ga (0.96-Xn) In (Xn+0.04) The As layer is grown at a temperature of 600~650℃, with a thickness of 500~1500nm, and the Zn doping concentration is 5E17~1E18cm. -3 .

[0055] Al 0.25 Ga (1-Xn) In Xn The As BSF layer 6 is grown at a temperature of 600~650℃, with a thickness of 100~300nm, and a Zn doping concentration of 1E18~3E18cm⁻¹. -3 .

[0056] p-type Ga (1-Xn) In Xn The As-based region 7 was grown at a temperature of 600–650 °C, with a thickness of 500–2000 nm, and a Zn doping concentration of 1E¹⁷–1E¹⁸ cm⁻¹. -3 .

[0057] n-type Ga (1-Xn) In Xn The As emitter region 8 is grown at a temperature of 600~650℃, with a thickness of 100~300nm, and a Si doping concentration of 1E18~5E18cm⁻¹. -3 .

[0058] The growth temperature of AlInP window layer 9 is 600~650℃, the thickness is 30~100nm, and the Si doping concentration is 1E18~8E18cm. -3 .

[0059] n-type Ga (1-Xn) In Xn The As cap layer 10 is grown at a temperature of 600~650℃, with a thickness of 50~100nm, and the Si doping concentration is 1E18~5E18cm⁻¹. -3 .

[0060] The material of hole transport layer 12 is selected from NiO. x doped NiO x The thickness is 10~30nm and is composed of one or any combination of two of the following: CuSCN and 4PACz-based monomolecular self-assembled layers.

[0061] The perovskite active layer 13 is a wide-bandgap perovskite material FA with a voltage of 1.78~1.9 eV. t MA y Cs z Pb 2-t-y-z I w Br 1-wThe thickness of the electron transport layer is 500~1500nm, wherein the FA content (t) is 0.45~0.9, the MA content (y) is 0~0.2, the Cs content (z) is 0.05~0.4, and t + y + z = 1, and the I content (w) is 0.6~0.85; the material of the electron transport layer 14 is selected from SnO2, 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline, and C 60 The material of the top electrode 15 is selected from one or any combination of two of the following: silver prepared by electron beam evaporation process and TCO material prepared by magnetron sputtering process, and the material of the top electrode 15 is selected from one or a ...

[0062] This embodiment also provides a method for preparing a III-V group compound / perovskite multi-junction tandem solar cell, including the following steps:

[0063] S1. Transfer the Ge substrate 1 into the MOCVD process; wherein, the Ge substrate 1 is a P-type Ge substrate or an N-type Ge substrate;

[0064] S2. Using a growth temperature of 600~650℃, a GaInP nucleation layer 2 is epitaxially grown on the upper surface of Ge substrate 1, with a thickness of 5~20nm and a Si doping concentration of 2E18~5E18cm⁻¹. -3 ;

[0065] S3. Using a growth temperature of 600~650℃, a GaInAs buffer layer 3 is epitaxially grown on the upper surface of the GaInP nucleation layer 2, with a thickness of 5~20nm and a Si doping concentration of 1E18~3E18cm. -3 ;

[0066] S4. Using a growth temperature of 600~650℃, a GaAs / AlGaAs tunnel junction 4 is epitaxially grown on the upper surface of the GaInAs buffer layer 3; the GaAs / AlGaAs tunnel junction 4 comprises a GaAs layer and an AlGaAs layer stacked sequentially; wherein the thickness of the GaAs layer is 10~20nm, and the Si doping concentration is 1E19~3E19cm. -3 The AlGaAs layer has a thickness of 5-15 nm and a C doping concentration of 3E19-9E19 cm⁻¹. -3 ;

[0067] S5. Using a growth temperature of 600~650℃, an epitaxial GB strain-relieving layer 5 is grown on the upper surface of the GaAs / AlGaAs tunnel junction 4; the GB strain-relieving layer 5 comprises N sequentially stacked Al 0.25 Ga (1-Xi) In Xi As layers and their stacking configurations are located on N Al layers. 0.25 Ga(1-Xi) In Xi Al at the top of As layer 0.25 Ga (0.96-Xn) In (Xn+0.04) As layer; where i = 1, 2, 3, ..., N, N Al 0.25 Ga (1-Xi) In Xi In the As layer, the In composition Xi ranges from 0.01 to 0.21, gradually changing along the stacking direction, and each Al layer... 0.25 Ga (1-Xi) In Xi The thickness of the As layers is consistent, or the thickness of each layer increases with the increase of the In content; all Al 0.25 Ga (1-Xi) In Xi The total thickness of the As layer is 1000~2000 nm, and the Zn doping concentration is 5E17~1E18 cm⁻¹. -3 The Al 0.25 Ga (0.96-Xn) In (Xn+0.04) The As layer is grown at a temperature of 600~650℃, with a thickness of 500~1500nm, and the Zn doping concentration is 5E17~1E18cm. -3 ;

[0068] S6. Al was epitaxially grown on the upper surface of GB strain-relief layer 5 at a growth temperature of 600~650℃. 0.25 Ga (1-Xn) In Xn As BSF layer 6, with a thickness of 100~300nm and a Zn doping concentration of 1E18~3E18cm. -3 ;

[0069] S7, using a growth temperature of 600~650℃, in Al 0.25 Ga (1-Xn) In Xn p-type Ga is epitaxially grown on the upper surface of BSF layer 6. (1-Xn) In Xn The As base region 7 has a thickness of 500~2000 nm and a Zn doping concentration of 1E17~1E18 cm⁻¹. -3 ;

[0070] S8. A growth temperature of 600~650℃ is used in p-type Ga... (1-Xn) In Xn n-type Ga is epitaxially grown on the upper surface of As base region 7. (1-Xn) In Xn The As emitter region 8 has a thickness of 100~300 nm and a Si doping concentration of 1E18~5E18 cm⁻¹. -3 ;

[0071] S9. A growth temperature of 600~650℃ is used in n-type Ga... (1-Xn) In Xn An AlInP window layer 9 with a thickness of 30~100nm is epitaxially grown on the upper surface of the As emitter region 8, and the Si doping concentration is 1E18~8E18 cm⁻¹. -3 ;

[0072] S10. Using a growth temperature of 600~650℃, n-type Ga is epitaxially grown on the upper surface of AlInP window layer 9. (1-Xn) In Xn The As cap layer 10 has a thickness of 50~100nm, and the Si doping concentration is 1E18~5E18cm⁻¹. -3 This process is used to prepare an epitaxial wafer, which is then transferred out from MOCVD, and a metal electrode is prepared on its lower surface to form an ohmic contact.

[0073] S11, in n-type Ga (1-Xn) In Xn A composite bonding layer is deposited on the upper surface of the As cap layer 10; specifically as follows: First, a composite bonding layer is deposited on the n-type Ga... (1-Xn) In Xn Au nanoparticle colloidal dispersion is spin-coated onto the upper surface of the As cap layer 10 to form a sparse and uniform Au nanoparticle conductive layer 1101. The Au nanoparticle conductive layer 1101 has a transmittance >90% and a thickness of 5~20 nm. Next, a PEDOT:PSS (PH1000) solution doped with 5% EG is spin-coated onto the upper surface of the Au nanoparticle conductive layer 1101 to completely cover the Au particles of the Au nanoparticle conductive layer 1101, forming a smooth and pinhole-free PEDOT:PSS interface buffer layer 1102 with a thickness of 20~60 nm. Finally, a dense and continuous MoO layer is formed on the upper surface of the PEDOT:PSS interface buffer layer 1102 using physical vapor deposition or atomic layer deposition. X Energy level matching layer 1103, the MoO X The thickness of the energy level matching layer 1103 is 5~15nm;

[0074] S12. A hole transport layer 12 is prepared on the upper surface of the composite bonding layer using a spin-coating process. The material of the hole transport layer 12 is selected from NiO. x doped NiO x One or any combination of two of CuSCN and 4PACz-based monomolecular self-assembled layers (4PACz-based SAM), with a thickness of 10~30nm;

[0075] S13. A perovskite active layer 13 is prepared on the upper surface of the hole transport layer 12 using a spin-coating process. The perovskite active layer 13 is a wide-bandgap perovskite material FA with a voltage of 1.78~1.9 eV. t MA y Cs z Pb 2-t-y-z I w Br 1-w Its thickness is 500~1500nm;

[0076] S14. An electron transport layer 14 is prepared on the upper surface of the perovskite active layer 13 using a spin-coating process. The material of the electron transport layer 14 is selected from SnO2, BCP (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline), C 60 One or any combination of two of them, with a thickness of 10~30nm;

[0077] S15. A top electrode 15 is fabricated on the electron transport layer 14. The material of the top electrode 15 is selected from one or a combination of two of the following: silver prepared by electron beam evaporation process and TCO materials (such as IZO, ITO, etc.) prepared by magnetron sputtering process. The thickness of the top electrode 15 is 100~250nm.

[0078] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope disclosed in the present invention, based on the technical solution and inventive concept of the present invention, shall fall within the scope of protection of the present invention.

Claims

1. A composite interconnecting layer for use in III-V compound / perovskite multi-junction tandem solar cells, characterized in that: It includes an Au nanoparticle conductive layer (1101), a PEDOT:PSS interface buffer layer (1102), and MoO, which are stacked sequentially from bottom to top. X Energy level matching layer (1103); the Au nanoparticle conductive layer (1101) has a transmittance >90% and a thickness of 5~20nm; the PEDOT:PSS interface buffer layer (1102) has a thickness of 20~60nm; the MoO X The thickness of the energy level matching layer (1103) is 5~15nm.

2. A III-V compound / perovskite multi-junction tandem solar cell, characterized in that: Includes a Ge substrate (1), a GaInP nucleation layer (2), a GaInAs buffer layer (3), a GaAs / AlGaAs tunnel junction (4), a GB strain relief layer (5), and Al 0.25 Ga (1-Xn) In Xn As BSF layer (6), p-type Ga (1-Xn) In Xn As base region (7), n-type Ga (1-Xn) In Xn As emitter region (8), AlInP window layer (9), n-type Ga (1-Xn) In Xn The structure comprises an As cap layer (10), a hole transport layer (12), a perovskite active layer (13), an electron transport layer (14), and a top electrode (15), and the composite interconnect layer as described in claim 1, wherein the Ge substrate (1), GaInP nucleation layer (2), GaInAs buffer layer (3), GaAs / AlGaAs tunnel junction (4), GB strain relief layer (5), and Al 0.25 Ga (1-Xn) In Xn As BSF layer (6), p-type Ga (1-Xn) In Xn As base region (7), n-type Ga (1-Xn) In Xn As emitter region (8), AlInP window layer (9), n-type Ga (1-Xn) In Xn The As cap layer (10), composite connection layer, hole transport layer (12), perovskite active layer (13), electron transport layer (14) and top electrode (15) are stacked sequentially from bottom to top.

3. The III-V compound / perovskite multi-junction tandem solar cell according to claim 2, characterized in that: The GaInP nucleation layer (2) is grown at a temperature of 600~650℃, has a thickness of 5~20nm, and a Si doping concentration of 2E18~5E18cm. -3 The GaInAs buffer layer (3) is grown at a temperature of 600~650℃, has a thickness of 5~20nm, and a Si doping concentration of 1E18~3E18cm. -3 .

4. The III-V compound / perovskite multi-junction tandem solar cell according to claim 2, characterized in that: The growth temperature of the GaAs / AlGaAs tunnel junction (4) is 600~650℃, and it includes GaAs layers and AlGaAs layers stacked sequentially; wherein the thickness of the GaAs layer is 10~20nm, and the Si doping concentration is 1E19~3E19cm. -3 The AlGaAs layer has a thickness of 5-15 nm and a C doping concentration of 3E19-9E19 cm⁻¹. -3 .

5. The III-V compound / perovskite multi-junction tandem solar cell according to claim 2, characterized in that: The GB strain relief layer (5) comprises N sequentially stacked Al layers. 0.25 Ga (1-Xi) In Xi As layers and their stacking configurations are located on N Al layers. 0.25 Ga (1-Xi) In Xi Al at the top of As layer 0.25 Ga (0.96-Xn) In (Xn+0.04) As layer; where i = 1, 2, 3, ..., N, N Al 0.25 Ga (1-Xi) In Xi In the As layer, the In composition Xi ranges from 0.01 to 0.21, gradually changing along the stacking direction, and each Al layer... 0.25 Ga (1-Xi) In Xi The thickness of the As layers is consistent, or the thickness of each layer increases with the increase of the In content; Al 0.25 Ga (1-Xi) In Xi The growth temperature of the As layer is 600~650℃, and all Al 0.25 Ga (1-Xi) In Xi The total thickness of the As layer is 1000~2000 nm, and the Zn doping concentration is 5E17~1E18 cm⁻¹. -3 The Al 0.25 Ga (0.96-Xn) In (Xn+0.04) The As layer is grown at a temperature of 600~650℃, with a thickness of 500~1500nm, and the Zn doping concentration is 5E17~1E18cm. -3 .

6. The III-V compound / perovskite multi-junction tandem solar cell according to claim 2, characterized in that: The Al 0.25 Ga (1-Xn) In Xn The As BSF layer (6) is grown at a temperature of 600~650℃, with a thickness of 100~300nm, and a Zn doping concentration of 1E18~3E18cm. -3 The p-type Ga (1-Xn) In Xn The As-based region (7) is grown at a temperature of 600~650℃, with a thickness of 500~2000nm, and a Zn doping concentration of 1E17~1E18 cm⁻¹. -3 The n-type Ga (1-Xn) In Xn The As emitter region (8) is grown at a temperature of 600~650℃, with a thickness of 100~300nm, and the Si doping concentration is 1E18~5E18cm. -3 The growth temperature of the AlInP window layer (9) is 600~650℃, the thickness is 30~100nm, and the Si doping concentration is 1E18~8E18cm. -3 The n-type Ga (1-Xn) In Xn The As cap layer (10) is grown at a temperature of 600~650℃, with a thickness of 50~100nm, and the Si doping concentration is 1E18~5E18cm. -3 .

7. The III-V compound / perovskite multi-junction tandem solar cell according to claim 2, characterized in that: The hole transport layer (12) is made of NiO. x doped NiO x The thickness is 10~30nm and is composed of one or any combination of two of the following: CuSCN and 4PACz-based monomolecular self-assembled layers.

8. The III-V compound / perovskite multi-junction tandem solar cell according to claim 2, characterized in that: The perovskite active layer (13) is a wide-bandgap perovskite material FA with a voltage of 1.78~1.9 eV. t MA y Cs z Pb 2-t-y-z I w Br 1-w Its thickness is 500~1500nm, wherein the FA content t is 0.45~0.9, the MA content y is 0~0.2, the Cs content z is 0.05~0.4, and t+y+z=1, and the I content w is 0.6~0.85; the material of the electron transport layer (14) is selected from SnO2, 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline, C 60 The material of the top electrode (15) is selected from one or any combination of two of the following: silver prepared by electron beam evaporation process and TCO material prepared by magnetron sputtering process, and the material of the top electrode (15) is selected from one or a ...

9. A method for preparing a III-V compound / perovskite multi-junction tandem solar cell according to any one of claims 2 to 8, characterized in that: Including steps, S1. Transfer the Ge substrate (1) into the MOCVD; wherein the Ge substrate (1) is a P-type Ge substrate or an N-type Ge substrate; S2. Using a growth temperature of 600~650℃, a GaInP nucleation layer (2) is epitaxially grown on the upper surface of the Ge substrate (1), with a thickness of 5~20nm and a Si doping concentration of 2E18~5E18cm. -3 ; S3. Using a growth temperature of 600~650℃, a GaInAs buffer layer (3) is epitaxially grown on the upper surface of the GaInP nucleation layer (2), with a thickness of 5~20nm and a Si doping concentration of 1E18~3E18cm. -3 ; S4. Using a growth temperature of 600~650℃, a GaAs / AlGaAs tunnel junction (4) is epitaxially grown on the upper surface of the GaInAs buffer layer (3); the GaAs / AlGaAs tunnel junction (4) includes a GaAs layer and an AlGaAs layer stacked sequentially; wherein, the thickness of the GaAs layer is 10~20nm, and the Si doping concentration is 1E19~3E19cm. -3 The AlGaAs layer has a thickness of 5-15 nm and a C doping concentration of 3E19-9E19 cm⁻¹. -3 ; S5. Using a growth temperature of 600~650℃, a GB strain relief layer (5) is epitaxially grown on the upper surface of the GaAs / AlGaAs tunnel junction (4); the GB strain relief layer (5) comprises N sequentially stacked Al 0.25 Ga (1-Xi) In Xi As layers and their stacking configurations are located on N Al layers. 0.25 Ga (1-Xi) In Xi Al at the top of As layer 0.25 Ga (0.96-Xn) In (Xn+0.04) As layer; where i = 1, 2, 3, ..., N, N Al 0.25 Ga (1-Xi) In Xi In the As layer, the In composition Xi ranges from 0.01 to 0.21, gradually changing along the stacking direction, and each Al layer... 0.25 Ga (1-Xi) In Xi The thickness of the As layers is consistent, or the thickness of each layer increases with the increase of the In content; all Al 0.25 Ga (1-Xi) In Xi The total thickness of the As layer is 1000~2000 nm, and the Zn doping concentration is 5E17~1E18 cm⁻¹. -3 The Al 0.25 Ga (0.96-Xn) In (Xn+0.04) The As layer is grown at a temperature of 600~650℃, with a thickness of 500~1500nm, and the Zn doping concentration is 5E17~1E18cm. -3 ; S6. Using a growth temperature of 600~650℃, Al was epitaxially grown on the upper surface of the GB strain release layer (5). 0.25 Ga (1-Xn) In Xn As BSF layer (6), with a thickness of 100~300nm and Zn doping concentration of 1E18~3E18cm. -3 ; S7, using a growth temperature of 600~650℃, in Al 0.25 Ga (1-Xn) In Xn p-type Ga is epitaxially grown on the upper surface of the As BSF layer (6). (1-Xn) In Xn The As base region (7) has a thickness of 500~2000 nm and a Zn doping concentration of 1E17~1E18 cm⁻¹. -3 ; S8. A growth temperature of 600~650℃ is used in p-type Ga... (1-Xn) In Xn n-type Ga is epitaxially grown on the upper surface of the As base region (7). (1-Xn) In Xn The As emitter region (8) has a thickness of 100~300 nm and a Si doping concentration of 1E18~5E18 cm⁻¹. -3 ; S9. A growth temperature of 600~650℃ is used in n-type Ga... (1-Xn) In Xn An AlInP window layer (9) with a thickness of 30~100nm is epitaxially grown on the upper surface of the As emitter region (8), and the Si doping concentration is 1E18~8E18 cm⁻¹. -3 ; S10. Using a growth temperature of 600~650℃, n-type Ga is epitaxially grown on the upper surface of the AlInP window layer (9). (1-Xn) In Xn The As cap layer (10) has a thickness of 50~100nm and the Si doping concentration is 1E18~5E18cm. -3 An epitaxial wafer is thus prepared, and then the epitaxial wafer is taken out from MOCVD, and a metal electrode is prepared on its lower surface to form an ohmic contact. S11, in n-type Ga (1-Xn) In Xn A composite bonding layer is deposited on the upper surface of the As cap layer (10); S12. A hole transport layer (12) is prepared on the upper surface of the composite bonding layer by spin coating. The material of the hole transport layer (12) is selected from NiO. x doped NiO x One or any combination of two of the following: CuSCN and 4PACz-based monomolecular self-assembled layers, with a thickness of 10~30 nm; S13. A perovskite active layer (13) is prepared on the upper surface of the hole transport layer (12) by spin coating. The perovskite active layer (13) is a wide-bandgap perovskite material FA with a voltage of 1.78~1.9 eV. t MA y Cs z Pb 2-t-y-z I w Br 1-w Its thickness is 500~1500nm; S14. An electron transport layer (14) is prepared on the upper surface of the perovskite active layer (13) using a spin-coating process. The material of the electron transport layer (14) is selected from SnO2, 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline, C 60 One or any combination of two of them, with a thickness of 10~30nm; S15. A top electrode (15) is prepared on the electron transport layer (14). The material of the top electrode (15) is selected from one or a combination of two of silver prepared by electron beam evaporation process and TCO material prepared by magnetron sputtering process, and its thickness is 100~250nm.

10. The method for preparing a III-V compound / perovskite multi-junction tandem solar cell according to claim 9, characterized in that: In step S11, firstly in n-type Ga (1-Xn) In Xn Au nanoparticle colloidal dispersion is spin-coated onto the upper surface of the As cap layer (10) to form a uniform Au nanoparticle conductive layer (1101). The transmittance of the Au nanoparticle conductive layer (1101) is >90%, and the thickness is 5~20 nm. Next, a PEDOT:PSS solution doped with 5% EG is spin-coated onto the upper surface of the Au nanoparticle conductive layer (1101) to completely cover the Au particles of the Au nanoparticle conductive layer (1101), forming a smooth, pinhole-free PEDOT:PSS interface buffer layer (1102). The thickness of the PEDOT:PSS interface buffer layer (1102) is 20~60 nm. Finally, a continuous MoO layer is formed on the upper surface of the PEDOT:PSS interface buffer layer (1102) using physical vapor deposition or atomic layer deposition. X Energy level matching layer (1103), the MoO X The thickness of the energy level matching layer (1103) is 5~15nm.